论新加坡翻译教育政策在中学阶段的演变与发展 = Evolution and development of translation education in the context of Singapore's secondary education landscape - 贝恩萱 Pui, Avis EnXuan (Nanyang Technological University, 2024)
基于新加坡特殊的语言和社会环境，双语教育一直是我国教育体系的核心政策。在全球化的背景下，本地的翻译需求日益增长，导致语言服务人才的培养越发得到重视。然而，我国的翻译质量欠佳、翻译人才储备不足等现象，都揭示了新加坡的翻译发展环境并不理想。对此，教育部于2010年就开始着力发展本地中学阶段的翻译教育，希望能够继续培育年轻一代的双语人才。本文聚焦我国中学翻译教育不同阶段的发展背景，并关注近年来翻译课程在现代化过程中的革新等新计划的推出和试行，反映其翻译教学的最新走向。通过对目前发展概况的回顾与总结，文章最后提出了对高中翻译课程的未来展望，旨在突显翻译教育在培养年轻一代语言服务人才所起到的重要作用。Bilingual education has long been a cornerstone of Singapore's education system due to our country's unique linguistic and social context. With globalization, the demand for translation services has also surged, underscoring the need to nurture more language talents. However, the subpar translation quality and inadequacy of translation talents available have highlighted the less-than-ideal translation environment in Singapore. In response, the Ministry of Education has introduced translation as a subject at the post-secondary level since 2010, aiming to groom the next generation of bilingual talents. This paper examines the different stages of translation education in the context of Singapore's secondary education landscape and explores the new initiatives and changes made to the curriculum as a result of modernization in recent years, reflecting evolving trends in the teaching of translation. By reviewing the current curriculum arrangement, the paper concludes with suggestions for the future of translation education and emphasizes its pivotal role in nurturing the next generation of language talents.